Marriage Equality Advocacy from the Trenches - Bonauto, Mary; Esseks, James (Columbia Journal of Gender and Law, 2015)
James Esseks [JE]: Hi everybody. Mary and I thought that since we work together all the time, we would go back and forth to talk about the evolution of the marriage equality movement. We’re going to try and cover a lot, and it’s going to be a bit of a mad dash, but we will do our best to make it comprehensible. We’ve both been doing this for a long time but Mary has really been doing this for a long time. Mary, you’ve been gay for pay for how many years?